Building Capacity and Infrastructure at Hospitals Implementing Minimally Invasive Tissue Sampling: Experience and Lessons Learned From Nepal, Rwanda, and Tanzania. (15th December 2021) - Subedi, Nuwadatta; Bhattarai, Suraj; Mremi, Alex; Ntakirutimana, Gervais; Ndayisaba, Marie Claire; Rugwizangoga, Belson; Mbarushimana, Djibril; Hategekimana, Elisée; Tuyizere, Vestine; Paganelli, Christina
Abstract: Background: Minimally invasive tissue sampling (MITS) is a useful tool to determine cause of death in low- and middle-income countries (LMICs). In 2019 the MITS Surveillance Alliance supported the implementation of small-scale postmortem studies using MITS in several LMICs. Methods: In this article we describe the preparations, challenges, and lessons learned as part of implementing MITS across 4 study sites in 3 countries: Nepal, Rwanda, and Tanzania. We describe the process for building capacity to conduct MITS, which consisted of training in MITS sample collection, individual site assessment to determine readiness and gaps prior to implementation, site visits as sites began implementation of MITS, and feedback based on remote evaluation of histology slides via an online portal. Results: The 4 study sites each conducted 100 MITS, for a total of 400. All 4 sites lacked sufficient infrastructure and facilities to conduct MITS, and upgrades were required. Common challenges faced by sites included that clinical autopsies were neither routinely conducted nor widely accepted. Limited clinical records made cause of death determination more difficult. Lessons learned included the importance of sensitization of the community and medical staff to MITS to enhance understanding and increase consent. Conclusions: The study sites accomplished MITS and utilized the available support systems to overcome the challenges. The quality of the procedures was satisfactory and was facilitated through the organized capacity-building programs.